Pernikahan Dini dan Budaya - Saskara, Ida Ayu Nyoman (Jurnal Ekonomi Kuantitatif Terapan, 2018)
Early marriage is still a common phenomenon in Indonesia. This phenomenon is motivated by various factors such as social, economic and cultural. This study aims to examine the role of cultural factors on the occurrence of early marriage in Indonesia. The culture proxyed by two forms, first, ethnicity background in the household and second, the matchmaking process. The analysis used Indonesia Life Survey (IFLS) data in 2014 with logistic model and ordinary least square (OLS). Results show that ethnic background has a very important role in influencing early marriage. Children from Javanese, Sundanese, Madurese, Sasak and Betawi ethnic have a tendency to marry earlier than other tribes. The study also proves that matchmaking process is a significant factor that encourages early marriage. Children with matchmaking process do marriage at a younger age than children who choose their own partner (without matchmaking process). Keywords: J12 marriage; J16 Economics of gender